Harmonic suppression control strategy of distribution networks based on the distributed power flow controller - Zhu, Chengzhi; Qiu, Peng (Frontiers in Energy Research, 2024)
New energy and multiple loads, such as distributed wind–solar storage and charging, are connected to the distribution network through power electronic converters, which increases the harmonic content in the distribution network and causes operational safety risks. In this paper, the mathematical model of harmonic current and harmonic power content in a distribution network is constructed by an equivalent circuit and vector diagram. The distributed power flow controller is proposed for harmonic control of the distribution network. The mathematical expressions of the harmonic current and harmonic power based on a distributed power flow controller are constructed, and the control strategy of the distributed power flow controller for harmonic control is proposed. The simulation results show that the proposed method can effectively suppress the fifth and seventh harmonics of the distribution network.